Characteristics and postnatal development of the acid lipase activity of the rat small intestine. - Coates, P M (1977)
Acid lipase was identified in the rat small intestine by using esters of 4-methylumbelliferone as substrates. Maximum activity towards the oleate ester was found at pH 4.0. In adult animals, the activity of acid lipase exhibited both latency and sedimentability, indicating a lyosomal localization. The activity of acid lipase was practically the same along the height of the villus, thus paralleling the distribution of acid beta-galactosidase. In adult rats, the activity of acid lipase in proximal (jejunum) and middle (mid-jejunum) sections of the small intestine was practically the same and exceeded the activity in the distal (ileum) section by a factor of 2. In suckling rats, the activity of the enzyme in the mid-jejunum exceeded that in the jejunum and ileum by 2.5- and 1.5-fold respectively. During postnatal development, the acid lipase activity of the mid-jejunum showed a peak between days 10 and 15, at which time it exceeded the adult mid-jejunum activity by 5--6-fold.